Hubungan Sikap Ibu Dengan Praktek Pemberian Mp-Asi (Makanan Pendamping Air Susu lbu) Di Posyandu Dusun Krajan Desa Karangpatihan Kecamatan Balong Kabupaten Ponorogo - Rijayanti, Ria; Indatul Laili, Siti (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstractThe greater it is and increasing Babys age then nutritional needs to meet energy needs. Then there needs lo be extra energy from food other than ASI known as J1P-ASI. The purpose of this research was to knowing relationship mothers altitude with practice of giving MP- AS! in Posyandu, Krajan hamlet, Karangpatihan Village, Balong District orPonorogo. The research design used cross-sectional. The population in this research arc all Mothers with babies 7 months- I 2 months in Posyandu, Krajan hamlet, Karangpatihan Village, Balong District of Ponorogo a number of 32 respondents. The sampel was all mothers with babies 7 months - 12 months in Posyandu, Krajan hamlet, Karangpatihan Village, Balong District of Ponorogo a number of 32 respondents. with total sampling teckhnic. The instrument in this research used to assess attitudes and practice or giving MP- ASI is a questionnaire. The time of this research 18 Juli 20 I 6. Analyzing data used was cross table frekuensi distribution. The results showed that most respondents 12 respondents (37%) who have a positive attitude then the practice of giving the MP-AS! is positive. This shows that increasingly positive attitude of a person then tend lo lake action that is positive inside practice of giving MP- AST.Keyword: Altitude, Practice of giving, MP-AS!